2015
DOI: 10.1134/s1063773715050060
|View full text |Cite
|
Sign up to set email alerts
|

Determining the nature of faint X-ray sources from the ASCA Galactic center survey

Abstract: Chandra, XMM-Newton, and XRT/Swift X-ray data have been used to improve the positions of the optical counterparts to these sources. Thereafter, we have carried out a series of spectroscopic observations of the established optical counterparts at the RTT-150 telescope. Analysis of X-ray and optical spectra as well as photometric measurements in a wide wavelength range based on optical and infrared catalogs has allowed the nature of the program sources to be determined. Two X-ray objects have been detected in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…SBS X34 (Swift J174023.9-285647) matches AX J1740.4-2856, which was identified with the nearby (56 pc), spectrally normal M dwarf 2MASS J17402384-2856527 by Lutovinov et al (2015). Optical flares up to V = 9 (from quiescent V = 13) were seen from 2MASS J17402384-2856527 in INTEGRAL Optical Monitor data.…”
Section: X-rays From Stellar Chromospheric Activitymentioning
confidence: 83%
“…SBS X34 (Swift J174023.9-285647) matches AX J1740.4-2856, which was identified with the nearby (56 pc), spectrally normal M dwarf 2MASS J17402384-2856527 by Lutovinov et al (2015). Optical flares up to V = 9 (from quiescent V = 13) were seen from 2MASS J17402384-2856527 in INTEGRAL Optical Monitor data.…”
Section: X-rays From Stellar Chromospheric Activitymentioning
confidence: 83%
“…In the previous paper (Krivonos et al 2012), we pre- Lutovinov et al 2013b, for details). A number of multi-wavelength follow-up observations were initiated to unveil the nature of these unclassified objects (Karasev et al 2012;Masetti et al 2013;Revnivtsev et al 2013;Zolotukhin & Revnivtsev 2015;Lutovinov et al 2013aLutovinov et al , 2015Tomsick et al 2015Tomsick et al , 2016aClavel et al 2016;Burenin et al 2016;Rahoui et al 2017) which led to the classification of 11 sources (shown by solid red circles in Fig. 1), rising the total survey identification completeness from ∼92% to ∼94%.…”
Section: Introductionmentioning
confidence: 99%
“…All but SBS X103 have soft Swift/XRT spectra. We quote some key information below, from the Two Micron All Sky Survey (2MASS, Skrutskie et al 2006) SBS X34 (Swift J174023.9−285647) matches AX J1740.4−2856, which was identified with the nearby (56 pc), spectrally normal M dwarf 2MASS J17402384−2856527 by Lutovinov et al (2015). Optical flares up to V = 9 (from quiescent V = 13) were seen from 2MASS J17402384−2856527 in INTEGRAL Optical Monitor data.…”
Section: X-rays From Stellar Chromospheric Activitymentioning
confidence: 99%